Experiments with Teaching Methodologies - Singh, Navneet Pratap (Journal of Engineering Education Transformations, 2025)
This study uses the backdrop of history of education and development of engineering education in the country to highlight, how the newly introduced subject of research skills is handled by the author. The study reminisces how India had once been the centre of learning. The paper analyzes the kind of teaching and research methodologies that might have existed in ancient India so that well recognized sciences like Yoga and Ayurveda developed in the country. The paper discusses about the faulty practices that have crept in the way engineering education is imparted to the students. Finally the paper discusses about the way this author taught the subject of research skills so that all the three domains of the bloom’s taxonomy namely cognitive, affective and psychomotor were taken care of. This is a report about teaching of a new subject of research skills to post graduate students. It signals that there have to be attempts to get rid of the ineffective practices that have crept into the way engineering education is imparted. Students have to be prepared for facing real life problems.